2021
DOI: 10.1002/fsn3.2406
|View full text |Cite
|
Sign up to set email alerts
|

1‐Methylcyclopropene (1‐MCP) retards the senescence ofPteridium aquilinum var. latiusculumby regulating the cellular energy status and membrane lipid metabolism

Abstract: Pteridium aquilinum var. latiusculum (PA) is a popular fern species in the Athyriaceae family that is widely distributed in Northeast China.It is rich in nutrients and exhibits the abilities to promote the growth and development of children, improve body immunity, strengthen memory, and delay the aging of the brain (Yamada et al., 2007).Because of its classification as a natural food and its abundance of nutrients, it has attracted increasing numbers of consumers in recent years. In 2015, the consumption of wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…As a result, 1-MCP is effective in maintaining fruit quality, reducing chilling injuries during the storage period and extending the shelf-life of some climacteric and non-climacteric fruit [13][14][15][16][17][18]. Furthermore, Xu et al [16] and Zhang et al [8], in previous studies, demonstrated a positive effect of 1-MCP on the quality and antioxidant enzyme activity, correlating 1-MCP treatment with the expression of genes related to phenolic metabolism.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…As a result, 1-MCP is effective in maintaining fruit quality, reducing chilling injuries during the storage period and extending the shelf-life of some climacteric and non-climacteric fruit [13][14][15][16][17][18]. Furthermore, Xu et al [16] and Zhang et al [8], in previous studies, demonstrated a positive effect of 1-MCP on the quality and antioxidant enzyme activity, correlating 1-MCP treatment with the expression of genes related to phenolic metabolism.…”
Section: Introductionmentioning
confidence: 91%
“…Pears and some fresh fruits continue to ripen after harvest, and this process not only speeds up product maturation but also affects their texture, aroma and composition and shortens their shelf-life [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Plant microbiomes consist of complex communities of potentially mutualistic, commensal, and pathogenic microbes colonizing the same niches in plants, including bacteria (such as Bacillus spp., Staphylococcus spp., Pseudomonas spp. and gram-negative bacilli, and yeasts and molds) that have diverse aspects of impacts on plant growth, health, and evolution [ 12 , 13 ]. The microbes that constitute the fruit microbiome can colonize the fruit either vertically, as endophytes that live within plant tissues, or horizontally from the rhizosphere, or through mixed colonization [ 14 ].The fruit microbiota might be especially important during crop storage by preventing or favoring rots, or quality loss due to sprouting, water loss, or else spoilage.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, healthy fruits have many microbes on their surfaces but can usually inhibit their growth until after harvest [ 6 ]. Ripening weakens cell walls and decreases the amounts of antifungal chemicals in fruits, and physical damage during harvesting causes breaks in outer protective layers of fruits that spoilage organisms can exploit [ 13 ]. Molds are tolerant of acidic conditions and low water activity and are involved in spoilage of mango, banana, citrus fruits, papaya, apples, and other fruits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation